Persekongkolan Tender Pelabuhan Nusa Penida: Faktor, Dampak, dan Peran KPPU - Asa, M. Fanshurullah; Aprilia, Sonia (Komisi Pengawas Persaingan Usaha, 2025)
One of the tender collusion cases that occurred was the procurement of goods and services in the port construction sector of Nusa Penida, Bali, in the 2022 fiscal year. This study aims to analyze the factors causing collusion, its impacts, and stakeholders’ perceptions of the Indonesian Competition Commission (KPPU). The research applies a quantitative approach using primary data collected through questionnaires distributed to KPPU staff and external parties involved in the Nusa Penida port collusion case. Secondary data were obtained from official KPPU documents regarding the case. The data were then processed using Statistical Package for the Social Sciences (SPSS) version 25. Overall, the analysis shows that the independent variables have a very strong influence on the dependent variable, with an Adjusted R Square value of 0.988, meaning 98%. The implementation yielded an average score of 28, falling into the “adequate” category. Validity and reliability tests also proved high, with a Cronbach’s Alpha value of 0.956. The variables that have a positive influence are Structure (X1), Behavior (X2), and Institutional (X4), while the variables that negatively influence are Performance (X3) and Demand Factors (X5). Therefore, this study highlights the importance of strengthening institutions and fostering ethical business behavior, as well as the need for control over performance and demand factors to create fair and healthy business competition.